2019
DOI: 10.1177/1545968319829454
|View full text |Cite
|
Sign up to set email alerts
|

Language as a Predictor of Motor Recovery: The Case for a More Global Approach to Stroke Rehabilitation

Abstract: Stroke is the third leading cause of death in the developed world and the primary cause of adult disability. The most common site of stroke is the middle cerebral artery (MCA), an artery that supplies a range of areas involved in both language and motor function. As a consequence, many stroke patients experience a combination of language and motor deficits. Indeed, those suffering from Broca's aphasia have an 80% chance of also suffering hemiplegia. Despite the prevalence of multifaceted disability in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 111 publications
(154 reference statements)
1
17
0
Order By: Relevance
“…In other words, the impact of L2 lexico-semantic processing on motor system has yet to be examined in brain-damaged populations. In monolinguals, some studies did look at the co-occurrence of language and motor impairment in developmental disorders (e.g., Hill, 2001; Sanjeevan et al, 2015) or brain-damaged patients (Desai et al, 2015; for a review see Anderlini et al, 2019).…”
Section: Studies On L2 Embodiment Serving Clinical Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the impact of L2 lexico-semantic processing on motor system has yet to be examined in brain-damaged populations. In monolinguals, some studies did look at the co-occurrence of language and motor impairment in developmental disorders (e.g., Hill, 2001; Sanjeevan et al, 2015) or brain-damaged patients (Desai et al, 2015; for a review see Anderlini et al, 2019).…”
Section: Studies On L2 Embodiment Serving Clinical Purposesmentioning
confidence: 99%
“…In Maitra et al (2006), for example, patients that had suffered a stroke had their movements facilitated with self-speech (i.e., self-vocalization). As Anderlini et al (2019) suggest, the choice of the type of therapeutic approach should consider both the language and motor systems and how they interact, especially when motor and language impairments coexist.…”
Section: Studies On L2 Embodiment Serving Clinical Purposesmentioning
confidence: 99%
“…Using a more conservative correction (ie, FWE), higher metabolism was identified in MCS+ compared with MCS− in the left middle temporal cortex, which has been associated to selective processing of speech, 26,27 semantic processing, 28,29 and word generation. 30 The FDR correction analysis also highlighted other language-related brain regions: the left angular gyrus, [31][32][33] the left middle frontal gyrus, [34][35][36][37][38] the left inferior frontal gyrus (pars opercularis), [39][40][41] the prefrontal and premotor cortex as well as supplementary motor area, 42 which are also involved in various motor functions. 43 These results are in line with previous research showing that the left middle temporal cortex and left angular gyrus could differentiate MCS subcategories at the subject level, 12 and that a preserved metabolism in these regions was associated with residual language comprehension in 3 postcoma patients.…”
Section: Discussionmentioning
confidence: 96%
“…These findings are in line with multiple studies that have shown that verbal dysfunction (presentation of aphasia) is a predictive factor for functional recovery and LS. [ 74 76 ] Aphasia is a predicting factor of functional motor outcome [ 75 ] and has been reported as a significant predictor of emotional distress, [ 77 ] loneliness, and social isolation. [ 78 ]…”
Section: Discussionmentioning
confidence: 99%